Molecular ME‐ToF‐SIMS yield as a function of DHB matrix layer thicknesses obtained from brain sections coated by sublimation/deposition techniques. (24th November 2015) - Körsgen, Martin; Pelster, Andreas; Vens‐Cappell, Simeon; Roling, Oliver; Arlinghaus, Heinrich F.
Abstract : Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) can be used to image biological samples with nanometer‐scale resolution, albeit with the drawback that it often cannot detect large molecular signals. One way to increase secondary ion molecular yield is to chemically modify the surface in the so‐called matrix‐enhanced SIMS (ME‐SIMS) approach, which is based on embedding analyte molecules in low‐weight organic matrices. In this study, a solvent‐free sample preparation technique was employed using sublimation/deposition for coating a mouse brain section with a thin layer of a 2, 5‐dihydroxybenzoic acid (DHB) matrix. Using this preparation technique, signal enhancements of up to a factor of 18 could be detected. It was found that the matrix layer thickness plays an important role in the efficiency of yield enhancement. Also, a complex influence of the matrix layer on various signals was observed. Copyright © 2015 John Wiley & Sons, Ltd.